Evaluation Operational Activities and Financial Statements of The Papua Pastoral Grocery Store: Evaluasi Kegiatan Operasional dan Laporan Keuangan Kios Pastoral Papua - Rahayu, Puji; Sutomo, Felisia; Faninda, Sandra; Mardiana, Mardiana; Kurnia, Tanto; Setiawan, Graciella Angelica (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Financial statements are structured representations that reflect business performance. The partner of this service activity, Papua Pastoral Grocery Store, faces various recording problems that are not in accordance with SAK EMKM, including recording inventory, fixed assets, debt, and profit and loss. This activity aims to increase partner capacity through training and mentoring, preparing Standar Operating Procedure, revising financial statement, compiling accurate manual books, compiling basic accounting pocketbooks. The result show an increase in partners understanding of basic financial accounting by 90%, progress in the application of record keeping in accordance with SAK EMKM, and improved operational efficiency through the application of new standard operation procedures. This program supports MSMEs in remote areas to be more financially independent.